Kit Radicaux Libres, a new innovative biological application for monitoring oxidative stress in pigs - Grazia Pastorelli; Massimo Faustini; Carlo Corino; Raffaella Rossi (Italian Journal of Animal Science, 2013)
Kit Radicaux Libres (KRL) test is a biological application, successfully applied on humans, helpful for the study of the total antiradical activity. In the present work, the first objective was to test on a subset of pig blood samples in order to determine the maximum time of storage able to provide reliable results. Blood samples were collected from 46 piglets and determinations were carried out on the blood samples after three h from collection (T1) and thereafter at 24 (T2) and 48 (T3) h. Successively blood samples from 313 piglets (171 castrated males and 142 females) were collected and analysed in order to determine reference intervals. Results are expressed as half-haemolysis time (HT50 in min), that is a reference point for blood susceptibility to free radical attack. Our findings showed that for samples analysed at T1 and T2 there were no significant changes but significantly increased values (P<0.05) were obtained when samples were analysed after 48 h from collection, underlining biological and analytical interference due to the hemolysis of the samples. The reference values found in the subjects, expressed as ET AL50 were 46.6-68.7 min (males) and 52.5-86.8 min (females) in RBC, 59.8-93.6 min (males) and 70.5-113.0 (females) in whole blood. In conclusion, a prolonged time (till +48 h) caused haemolysis, therefore the use of freshly collected blood is strictly recommended. The reference values obtained are considered to represent valid reference ranges for healthy pigs starting after weaning to 175 days of age under modern husbandry conditions.